# Stuck on simple formula rearranging

Announcements
#1
Hi

I'd be very grateful for any help. The question I'm trying to answer says :-

Rearrange the formula p(q-1) = q to make q the new subject.

The answer given is q = p/(p-1)

I don't understand how you get this answer...

Can anyone show the working please?

Thanks
0
6 years ago
#2
(Original post by andyuser727)
Hi

I'd be very grateful for any help. The question I'm trying to answer says :-

Rearrange the formula p(q-1) = q to make q the new subject.

The answer given is q = p/(p-1)

I don't understand how you get this answer...

Can anyone show the working please?

Thanks
First expand the left-hand-side. Then move both 'q' terms to the same side. Then take out a factor of q.

Have a go at this and post all your working if you get stuck.
2
#3
pq - p = q
pq - q = p
q(q - 1) = p
q = p / (q - 1)

OK excellent! Thanks. I still have questions tho. If you start substituting values for p and q, the formula looks wrong.

Eg. p = 2, q = 3
2(3 - 1) = 3
6 - 2 = 3
4 = 3 ?????
0
6 years ago
#4
(Original post by andyuser727)
pq - p = q
pq - q = p
q(q - 1) = p
q = p / (q - 1)

OK excellent! Thanks. I still have questions tho. If you start substituting values for p and q, the formula looks wrong.

Eg. p = 2, q = 3
2(3 - 1) = 3
6 - 2 = 3
4 = 3 ?????
take a look at the formulae (in bold)
0
6 years ago
#5
(Original post by andyuser727)
pq - p = q
pq - q = p
q(q - 1) = p
q = p / (q - 1)
There are a couple of mistakes in your working and answer but they might be typos.

OK excellent! Thanks. I still have questions tho. If you start substituting values for p and q, the formula looks wrong.

Eg. p = 2, q = 3
2(3 - 1) = 3
6 - 2 = 3
4 = 3 ?????
This equation isn't true for any p and q. You seem to have picked random values for the variables and expected them to satisfy the equation.

0
#6
pq - p = q
pq - q = p
q(p - 1) = p
q = p/(p - 1)

oops, sorry. Is that correct now?

I don't know why I was substituting random values. I get it now.

So if p = 3 then
q = 3/(3 - 1) then
q = 3/2
q = 1.5
1
6 years ago
#7
(Original post by andyuser727)
pq - p = q
pq - q = p
q(p - 1) = p
q = p/(p - 1)

oops, sorry. Is that correct now?

I don't know why I was substituting random values. I get it now.

So if p = 3 then
q = 3/(3 - 1) then
q = 1 2/3
Yes that's correct now.
0
X

new posts Back
to top
Latest

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### Poll

Join the discussion

They're better than I expected (8)
34.78%
They're exactly what I expected (7)
30.43%
They're lower than I expected (8)
34.78%